Ovarian Fibrothecoma: A Residual Malignant Case - Ratri Wulandari; Addin Trirahmanto; Ardhanu Kusumanto (Biomedika, 2025)
Ovarian fibrothecomas, sex cord-stromal tumors consisting of theca-like elements and fibrous tissue, are solid tumors of the ovary, accounting for 1–4.7% of all ovarian tumors. If the tumors cannot be differentiated between fibroma and thecoma, they are categorized as fibrothecoma. These solid tumors are common, but their malignant type is extraordinarily rare. Here we present a residual malignant ovarian fibrothecoma in a 67-year-old woman. This patient complained of abdominal mass, she previously had laparotomy four times and two series of chemotherapy with paclitaxel and carboplatin within 19 years. Despite these, she currently has a residual disease measuring 13.5 x 11.6 x10.8 cm. In this case report, we will discuss the management of malignant fibrothecoma based on the available literature